Toxicity analysis of ocular prosthesis acrylic resin with or without pigment incorporation in human conjunctival cell line - da Silva, Emily Vivianne Freitas [UNESP]; Goiato, Marcelo Coelho [UNESP]; Bonatto, Liliane da Rocha [UNESP]; de Medeiros, Rodrigo Antonio [UNESP]; Santos, Daniela Micheline dos [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Oliveira, Sandra Helena Penha de [UNESP] (Elsevier, 2016)
The aim of this study was to evaluate the influence of pigment incorporation on the cytotoxicity of ocular prosthesis N1 color acrylic resin. Nine samples were manufactured by heat-polymerization in water bath and divided into 3 groups: acrylic resin without pigment incorporation (group R), acrylic resin with pigment incorporation (group RP), and acrylic pigment (group P). Eluates formed after 72 h of sample immersion in medium were incubated with conjunctival cell line (Chang conjunctival cells) for 72 h. The negative control group consisted in medium without samples (group C). The cytotoxic effect from the eluates was evaluated using MTT assay (cell proliferation), ELISA assay (quantification of IL1β, IL6, TNF α and CCL3/MIP1α) and RT-PCR assay (mRNA expression of COL IV, TGF β and MMP9). Data were submitted to ANOVA with Bonferroni post-tests (p < 0.05). All groups were considered non-cytotoxic based on cell proliferation. However, resin with pigment incorporation showed significant IL6 quantity increase. Resin without pigment incorporation exhibited higher mRNA expression of COL IV, MMP9 and TGF β, however it was also observed for the negative control group. The materials exhibited divergent biological behavior. Despite the pigment incorporation that resulted in an increase of IL6, no cytotoxicity was observed based on cell proliferation.
Keywords: Acrylic resins; Biocompatibility testing; Dental material; Monomers; Ocular prosthesis